Depressive Symptoms and the Effectiveness of a Urate‐Lowering Therapy in a Clinical Trial. Issue 12 (20th November 2020) - Mrug, Sylvie; Orihuela, Catheryn; Rahn, Elizabeth; Mudano, Amy; Foster, Jeffrey; Saag, Kenneth; Gaffo, Angelo
Abstract : Objective: This ancillary study examined the impact of depressive symptoms on the effectiveness of a urate‐lowering therapy in the context of a clinical trial. Methods: Participants included 67 adults (ages 18–40) with elevated blood pressure who were enrolled in a double‐blind, randomized, crossover clinical trial evaluating the effectiveness of allopurinol (300 mg/d) versus placebo to decrease blood pressure. Depressive symptoms were measured at the beginning of each 4‐week phase with the Center for Epidemiological Studies Depression scale (CESD‐10). Serum urate (sUA) was assessed at the beginning and end of each treatment phase. Compliance to treatment was measured by having detectable oxypurinol levels. Linear regressions tested associations between depressive symptoms and change in sUA in each phase, adjusting for sex and race. Logistic regression predicted compliance from depressive symptoms. Results: Participants had a mean age of 27 years and were 64% male and 39% African American. sUA levels decreased during the allopurinol treatment period but did not change during the placebo period. Higher depressive symptoms at pretreatment were associated with an attenuated urate‐lowering response during the allopurinol phase (β = 0.24, p < 0.05), but had no effect on sUA changes during the placebo phase. Depressive symptoms were not associated with treatment compliance assessed by oxypurinol levels. Conclusion: Depressive symptoms were associated with reduced efficacy of allopurinol treatment for hyperuricemia in a clinical trial targeting hypertension. Studies evaluating the efficacy of urate‐lowering therapies may benefit from screening for depressive symptoms.